Analisis Peningkatan Efektivitas pada Perusahan Kargo dengan Metode Six Sigma DMAIC dan FMEA - Tyas Eka Kurnia; Sugiyanto (Fakultas Teknik Universitas Pancasila, 2021)
The PT. XYZ is engaged in freight forwarding which has its own aircraft fleet, this company still has problems with uncoordinated shipments resulting in the goods not being sent according to the specified time. In 2017, PT. XYZ received many complaints from customers using these services so that the company had to pay losses due to late delivery that occurred. Some customers even choose to use cargo shipping services from other companies. Six Sigma is a process improvement strategy, for example to eliminate waste, reduce costs and improve the effectiveness of all operational activities so that they can meet customer needs and expectations. The purpose of this research is that the goods produced can reach the predetermined quality standards, so that the cost of inspection can be as possible. The results of the study show that the factor that often affects is human factors.